Multi-Source Domain Adaptation Techniques for Mitigating Batch Effects: A Comparative Study - Panda, Rohan; Kalmady, Sunil Vasu; Greiner, Russell (Frontiers in Neuroinformatics, 2022)
The past decade has seen an increasing number of applications of deep learning (DL) techniques to biomedical fields, especially in neuroimaging-based analysis.Such DL-based methods are generally data-intensive and require large number of training instances, which might be infeasible to acquire from a single acquisition site, especially for data such as fMRI scans, due to the time and costs that they demand. We can attempt to address this issue by combining fMRI data from various sites, thereby creating a bigger heterogeneous datasets. Unfortunately, the inherent differences in the combined data, known as batch effects, often hampers learning a model. To mitigate this issue, techniques such as multi-source domain adaptation (MSDA) aim at learning an effective classification function that uses (learned) domain-invariant latent features. This paper analyzes and compares the performance of various popular MSDA methods (MDAN, DARN, MDMN, M$^3$SDA) at predicting different labels (illness, age and sex) of images from two public public rs-fMRI datasets: ABIDE and ADHD-200. It also evaluates the impact of various conditions such as:class imbalance, number of sites along with a comparison of the degree of adaptation of each of the methods, thereby presenting the effectiveness of MSDA models in neuroimaging-based applications.